What your third grader needs to know : fundamentals of a good third-grade education - Hirsch, E. D., Jr. (Eric Donald), 1928- (New York, N.Y. : Delta, 1994)
Supplemental guide to classroom education to help third graders progress in school and be effective in society.
I. Language arts. Stories and speeches ; Norse mythology ; Learning about language ; Learning about literature ; Sayings and phrases -- II. Geography, world civilization, and American civilization. World geography ; Geography of the Americas ; World civilization ; American civilization -- III. Fine arts. Music ; Visual arts -- IV. Mathematics. Third-grade mathematics ; Multiplication ; Division ; Numbers through hundred thousands ; Addition and subtraction ; Sums and differences of four-digit numbers ; Time, money, and graphs ; Measurement ; Geometry ; Multiplication-- part two ; Division-- part two ; Fractions -- Word problems -- V. Natural sciences. Life sciences ; The human body and health ; Physical sciences ; Stories of scientists.
Cover title: What your 3rd grader needs to know.
Includes index.
Keywords: Third grade (Education) -- Curricula -- United States; Curriculum planning -- United States